Acquired Haemophilia: Functional Study of Antibodies to Factor VIII - Allain, J P; Gaillandre, A; Frommel, D (Thrombosis and Haemostasis, 1981)
Factor VIII complex and its interaction with antibodies to factor VIII have been studied in 17 non-haemophilic patients with factor VIII inhibitor. Low VIII:C and high VIIIR.Ag levels were found in all patients. VIII:WF levels were 50% of those of VTIIRrAg, possibly related to an increase of poorly aggregated and electrophoretically fast moving VIIIR:Ag oligomers.Antibody function has been characterized by kinetics of VIII :C inactivation, saturability by normal plasma and the slope of the affinity curve. Two major patterns were observed:1) Antibodies from 6 patients behaved similarly to those from haemophiliacs by showing second order inhibition kinetics, easy saturability and steep affinity slope (> 1).2) Antibodies from other patients, usually with lower titres, inactivated VIII :C according to complex order kinetics, were not saturable, and had a less steep affinity slope (< 0.7). In native plasma, or after mixing with factor VIII concentrate, antibodies of the second group did not form immune complexes with the whole factor VIII molecular complex. However, dissociation procedures did release some antibodies from apparently low molecular weight complexes formed in vivo or in vitro. For appropriate management of non-haemophilic patients with factor VIII inhibitor, it is important to determine the functional properties of their antibodies to factor VIII.
Keywords: Auto-immune antibodies to factor VIII; Acquired haemophilia; Kinetics of factor VIII inhibition; Factor VIII molecular complex